Protoporphyrin IX Stimulates Melanogenesis, Melanocyte Dendricity, and Melanosome Transport Through the cGMP/PKG Pathway - Lv, Jinpeng; An, Xiaohong; Jiang, Songzhou; Yang, Ying; Song, Guoqiang; Gao, Rongyin (Frontiers in Pharmacology, 2020)
Protoporphyrin IX (PPIX) is a heterocyclic organic compound that is the last intermediate in the heme biosynthetic pathway. PPIX, due to its photodynamic effects, is utilized in the treatment of skin diseases. Furthermore, PPIX has been utilized as a melanogenesis-stimulating agent in various studies. However, the exact function and mechanism underlying PPIX action in melanocytes remain to be elucidated. In the present study, we sought to further investigate how PPIX affects melanocyte melanogenesis, and whether PPIX is involved in melanin transport. Our findings demonstrated that PPIX increased melanocyte dendricity and melanosome transport, in addition to increasing melanogenesis. PPIX functions primarily by activating the guanylate cyclase (GC) and cyclic guanosine 3', 5'-monophosphate/ protein kinase G (cGMP/PKG) signaling pathways. Once activated, these pathways increase tyrosinase activity and the expression of microphthalmia-associated transcription factor (MITF), tyrosinase, tyrosinase-related protein-1 and -2 (TRP-1, TRP-2), myosin Va, melanophinin, Ras-related protein Rab-27A (Rab27a), and cell division cycle 42 (Cdc42), promoting melanogenesis, melanocyte dendricity, and melanosome transport. Furthermore, the melanogenic effects of PPIX were confirmed in vivo in a zebrafish model system. Our results indicate that PPIX is not cytotoxic, and may, thus, be utilized as a pigmentation enhancer.